Analysis of Factors Affecting Regional Original Revenue in Bali Province - Putu Putri Mayra Dewi; I Nyoman Wahyu Widiana (International Journal of Economics, Management and Accounting, 2025)
Regional Original Revenue is one of the main indicators in assessing a region's financial independence in managing local finances. This study aims to analyze the simultaneous and partial influence that affects PAD in Bali Province, focusing on the number of tourists, tourist attractions, and the number of restaurants. The research method used is a quantitative approach with panel data regression analysis techniques. The data used is secondary data obtained from the Bali Province Central Bureau of Statistics and other relevant institutions. The results show that the number of tourists, tourist attractions, and the number of restaurants simultaneously have a significant effect on Regional Original Revenue in Bali Province. Partially, the number of tourists has a positive and significant effect on Regional Original Revenue, indicating that the higher the number of tourists, the greater their contribution to regional revenue. However, the number of tourist attractions has a negative and significant effect on Regional Original Revenue, suggesting that an increase in tourist attractions that is not optimally managed may reduce the effectiveness of regional revenue. Meanwhile, the number of restaurants has a positive and not have a significant impact on Regional Original Revenue, which may be due to tax management factors or the effectiveness of oversight in the sector. This study suggests that the regional government should improve the management and promotion of tourist destinations to attract more tourists, which would directly contribute to increasing Regional Original Revenue. Additionally, strategies to enhance local tax collection in the restaurant sector should be further evaluated to optimize their contribution to Regional Original Revenue.f Restaurants